Playing under the piano eaudiobook From downton to darkest peru. - Bonneville, Hugh (Books on Tape, 2022)
A moving, laugh-out-loud memoir from one of today’s best-loved British actors, whose credits include Downton Abbey , Notting Hill , and Paddington . From getting his big break as Third Shepherd in the school nativity play, to mistaking a Hollywood star for an estate agent, Hugh Bonneville creates a brilliantly vivid picture of a career on stage and screen. What is it like working with Judi Dench and Julia Roberts, or playing Robert De Niro’s right leg, or not being Gary Oldman, twice? A wickedly funny storyteller, Bonneville also writes with poignancy about his father’s dementia and of his mother, whose life in the secret service emerged only after her death. Whether telling stories of working with divas, Dames, or a bear with a penchant for marmalade, this is a richly entertaining account of his life as an actor.